1982
DOI: 10.2337/diacare.5.2.s4
|View full text |Cite
|
Sign up to set email alerts
|

Authenticity and Purity of Human Insulin (recombinant DNA)

Abstract: A summary of the exhaustive analyses of human insulin (recombinant DNA) shows chemical, structural, and biologic equivalence to pancreatic human insulin. The high degree of purity accounts for its lack of pyrogenicity and immunogenic contamination. Human insulin from both the proinsulin and chain combination methods is essentially identical. The role of proinsulin as an alternate route to human insulin, and as a new treatment for diabetes when used alone or in combination with human insulin or connecting pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

1983
1983
1999
1999

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 0 publications
0
16
0
2
Order By: Relevance
“…Human insulin of recombinant DNA origin is the first product of DNA technology which has become widely availabe for clinical trials and eventual use in patients. It is chemically identical to endogenous insulin and is free of pancreatic contaminants [4,7]. Preliminary short-term studies suggested that this insulin did provoke formation of IgE antibodies but was free of problems associated with clinical allergy [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human insulin of recombinant DNA origin is the first product of DNA technology which has become widely availabe for clinical trials and eventual use in patients. It is chemically identical to endogenous insulin and is free of pancreatic contaminants [4,7]. Preliminary short-term studies suggested that this insulin did provoke formation of IgE antibodies but was free of problems associated with clinical allergy [19].…”
Section: Discussionmentioning
confidence: 99%
“…Purified pork insulin was manufactured from pancreases supplied by slaughterhouses specializing in pork products and contained no detectable beef insulin (< 0.05%) and 2.25.+ 0.37 ppm of pork proinsulin. Human insulin (rDNA) and purified porcine insulin used for these studies have been fully characterized and compared previously [7].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, previous attempts by other investigators had suggested that bacterial expression of proinsulin resulted in very poor yields due to N-terminal degrada- tion [11]. We have therefore developed a procedure, based upon the work of investigators at Eli Lilly and elsewhere [9,13,14] to produce proinsulin.…”
Section: Discussionmentioning
confidence: 99%
“…These advantages include ease of maintaining bacterial cultures, high level expression of recombinant proteins, and the simplicity of E. coli genetics. In recent years, a number of attempts have been made to express both insulin and proinsulin in bacteria [9][10][11][12][13][14]. These attempts have included both expression of the B and A chains separately, and the expression of intact proinsulin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation